Studi Komparatif: Manajemen Diri pada Pasien Diabetes Mellitus Tipe II di Wilayah Perkotaan dan Pedesaan - Vernanda, Gilang Adi; Sari, Ike Wuri Winahyu (Penerbit Goodwood, 2024)
Purpose: Type II diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia that can cause complications if not treated. Therefore, self-management is required. One factor that influences self-management is the characteristics of one’s place of residence. By examining the different characteristics of urban and rural areas, self-management will, of course, differ. This study aimed to determine differences in self-management among patients with type II DM in urban and rural areas. Methodology: This study used a comparative analytical research design and a cross-sectional approach. The target respondents for this study were type II DM patients in the Puskesmas Mergangsan area who participated in the Bolo Gendis program and type II DM patients in the Puskesmas Pandak I area who participated in PROLANIS for DM. Using purposive sampling, the number of respondents in this study was 46, with 23 in each region. The Diabetes Self-Management Questionnaire (DSMQ) was used in this study. In this study, the bivariate test used was the independent t-test and Mann-Whitney test. Results: The results showed that there were differences in self-management among patients with type II DM in urban and rural areas (p=0.000). The mean score in rural areas was 38.04±5.381, while in urban areas it was 26.17±6.692 in the score range (0-48), so self-management in rural areas is better than in urban areas. There were significant differences in several aspects, including physical activity (p=0.001), glucose management (p=0.000), glucose diet (p=0.001), and health care (p=0.002). Contribution: According to the results, it is expected that puskesmas can improve the PROLANIS program by providing education on every aspect of self-management, so that there is no gap in self-management in urban and rural puskesmas.